Impacts of coagulation-flocculation treatment on the size distribution and bioavailability of trace metals (Cu, Pb, Ni, Zn) in municipal wastewater - Hargreaves, Andrew J.; Vale, Peter C. J.; Whelan, Jonathan; Alibardi, Luca; Constantino, Carlos; Dotro, Gabriela; Cartmell, Elise; Campo Moreno, Pablo (Elsevier, 2017)
This study investigated the impact of coagulation-flocculation treatment on metal form and bioavailability in municipal wastewater. Real humus effluent samples were separated into particulate, colloidal and truly dissolved fractions before and after treatment with either ferric chloride (FeCl3) or the biopolymer Floculan. Results revealed that both reagents effectively (≥48%) eliminated Cu, Pb and Zn from the particulate fraction and removed Cu and Zn from the colloidal fraction in conjunction with colloidal organic carbon (COC). Although organics in the truly dissolved fraction were resistant to removal, Floculan reduced Cu in this fraction by 72% owing to the complexation of free Cu ions to phenol and amino groups along the polymeric chains, revealing an additional removal pathway. In fact, COC removed in the CF process by Floculan was replaced with truly dissolved compounds, input as a result of this reagents organic composition. Floculan, therefore, reduced the soluble concentration of Cu and Zn without changing the DOC concentration, thus reducing the bioavailability of these metals in treated effluent. FeCl3 did not reduce the bioavailability of target metals, thus did not deliver any environmental benefit. This work provides important information for the selection and development of high performance coagulants to improve metal removal.
Keywords: Particle fractions; Colloids; Wastewater; Bioavailability; Coagulation